Meningkatkan Keaktifan, Komunikasi, Kolaborasi, Dan Hasil Belajar Matematika Siswa Melalui Penerapan Model PBL - Arbain Arbain; Novi Anjani; La Ode Sirad; Halidin Halidin (FKIP Universitas Palangka Raya, 2024)
The underlying basis of this research is the identification of several issues at MTS An-Nur Rantebaru, namely the traditional nature of teaching, limited learning resources relying on teacher explanations, students' difficulties in solving mathematical problems, and the average mathematics learning outcomes of students falling below the Minimum Mastery Criteria (MMC). This classroom action research was conducted as an effort to improve teaching with the aim of enhancing students' engagement, communication, collaboration, and mathematics learning outcomes through the application of the PBL model, combined with lecture methods, peer teaching, and discussions, as well as the use of worksheets. The subjects of this research were 25 seventh-grade students at MTS An-Nur Rantebaru. Data analysis techniques involved qualitative and quantitative descriptive analysis. The results of the research showed an increase in both student and teacher activities in the learning process in each meeting of every cycle. Likewise, students' engagement, communication, collaboration, and learning outcomes improved in each meeting. The research was deemed successful in the second cycle with the following achievements: the implementation of teaching activities for teachers reached 95.24%; student activities reached 82.22%; 80% of students were categorized as active or highly active; 84% of students were communicative or highly communicative; 88% of students were collaborative or highly collaborative; and 84% of students met or exceeded the MMC score.